The Effect of Dependency on Repurchase Intention and Technostress - Antonius Satria Hadi (Jurnal Maksipreneur, 2018)
This study aims to investigate the effect of convenience to dependency toward smartphone, the effect of social need to dependency toward smartphone, the effect of social influence to dependency toward smartphone, the effect of dependency toward smartphone on repurchase intention, and the effect of dependency toward smartphone on technostress. This research have five hypotheses. Data were collected from 170 respondents which got from questionnaire distributed to graduate degree students of Universitas Gadjah Mada, Yogyakarta. Based of the data collection, this analysis using structural equation modeling technique with software LISREL 8.72. The results of this research showed that convenience, social need, and social influence have positive and significant effects to dependency, while the dependency have positive and significant effects to repurchase intention and technostress. All (five) hypotheses on this research have been accepted. Each of those hypotheses discussed in detail through this article.